Development of a standard set of key work-related outcomes for use in practice for patients with cardiovascular disease: a modified Delphi study - Marije E. Hagendijk; Nina Zipfel; Jan L. Hoving; Marijke Melles; Philip J. van der Wees; Sylvia J. van der Burg-Vermeulen (Journal of Patient-Reported Outcomes)
Abstract Background To facilitate the maintenance or resumption of participation in work for patients with cardiovascular disease (CVD), there is a need for high-quality work-focused healthcare. According to the concept of value-based healthcare, quality of care can be enhanced by understanding the outcomes that matter most to patients. However, a major challenge in assessing quality of work-focused healthcare in practice is the lack of consensus on which work-related outcomes should be measured. Objective The objective of this study was to identify a standard set of key work-related outcomes for patients with CVD to be used in practice of work-focused healthcare in the Netherlands, including standardised outcome measures and associated case mix factors. This standard set is intended to assist occupational and other health professionals in delivering work-focused healthcare that meets a patient’s individual needs regarding work participation, and to enhance patients’ engagement in their own work-focused care process. Methods A 2-round RAND-modified Delphi process was conducted. The process included literature searches, consecutive research team meetings, and several meetings and rounds of voting by a working group. The working group consisted of patients with CVD (n = 6) and health professionals representing different stakeholders (n = 11) involved in work-focused healthcare for this patient population in the Netherlands. Consensus was reached over four phases: (1) establishing the scope of the standard set and defining the population, (2) prioritising and defining the outcome domains, (3) selecting the outcome measures for the most important domains, including clinical data and patient-reported data, and (4) selecting and defining case mix factors. Results A 23-item patient-reported questionnaire was developed, called the Value@WORK-Q23, including questions on nine work-related outcome domains considered most important for patients with CVD: (1) work participation, (2) physical work ability, (3) mental work ability, (4) suitable work, (5) support from the work environment, (6) flexibility of the work environment, (7) communication with the patient, (8) person-centredness, and (9) interdisciplinary communication. In addition, nine case mix variables was selected, comprising demographic-, disease-, and work factors. Conclusions The Value@WORK-Q23 provides guidance on measuring the most important work-related outcomes for patients with CVD. Using this work-related set in practice, in addition to existing disease-specific standard sets for CVD may facilitate the provision of high-value work-focused healthcare for this patient population.